CORRELATION BETWEEN OBESITY AND GESTATIONAL DIABETES MELLITUS FROM THE OBSTRETIC AND GYNAECOLOGY OUTPATIENT CLINIC OF DR. SOETOMO GENERAL HOSPITAL SURABAYA FROM 2015 TO 2017 - LIM KAH WEI, NIM011611133248 (2019)
Background: Obesity in mother is an important risk factor for the development of gestational diabetes mellitus. Gestational diabetes mellitus is defined as glucose intolerance of variable degree with onset or first recognition during pregnancy. Obesity in pregnancy is usually defined as a Body Mass Index (BMI) of 30 kg/m2 or more at the first antenatal consultation. BMI is a simple index of weight-for-height and is calculated by dividing a person’s weight in kilograms by the square of their height in meters (kg/m2). There are three different classes of obesity: BMI 30.0–34.9 (Class I); BMI 35.0–39.9 (Class 2); and BMI 40 and over (Class 3 or morbid obesity). Purpose: To identify the prevalence of obesity as a risk factor for gestational diabetes mellitus at Obstetric and Gynecologic Outpatient Clinic of Dr. Soetomo General Hospital Surabaya from 2015 to 2017. Method: This study will be a cross sectional study. This study aims to show a correlation between obesity in pregnant women and gestational diabetes mellitus by using medical records at Dr. Soetomo General Hospital Surabaya from January 2015 to December 2017.The results were analysed using SPSS software. Results: The sample size is 69. Chi-square measure of association showed the obesity and gestational diabetes mellitus (P-value > 0.05 ). The P-value shows not significant relationship between obesity status (BMI value above 30) for gestational diabetes mellitus status. Conclusion: There were no correlation between obesity and gestational diabetes mellitus. It shows that obesity as a risk factor for gestational diabetes mellitus is not significant.